Kala Pathar (Paraphenylenediamine): the Frequent and fatal poisoning - Sadia Imran, Syed Zulfiquar Ali Shah, Ishrat Bibi, Farheen Qadeer, Deeba Khan, Azmira, (Pakistan Journal of Medical & Health Sciences, 2024)
Pakistan doesn't keep exact records of deaths or suicides because it doesn't have any vital records. The world's average suicide death rate for both men and women in 2017 was 9.98 per 100,000 people. In Pakistan, the projected age-adjusted suicide rate is 4.4 per 100,000 people. Three countries that are close by have suicide death rates of 13.33, 5.73, and 7.55 per 100,000 people, respectively. Recent statistics show that self-harm is becoming a major public health issue in Pakistan, even though the estimated rate is still low1. About 96% of the people who live in Pakistan are Muslims. Like most major faiths, Islam says that suicide is a sin that can't be forgiven. This could be a big reason why people don't commit suicide, as shown by the fact that rates are usually much lower in Muslim countries than in non-Muslim countries. Because of religious beliefs, both self-harm and suicide are illegal in Pakistan and can lead to jail time and fines. This is another reason why people don't want to commit suicide2,3. For teens and young adults ages 15 to 29, self-harm is the second most common reason for death, after road traffic accidents some places in Africa and Asia, like Pakistan, are seeing more and more people intentionally hurting themselves by taking paraphenylenediamine (PPD)4.